2019
DOI: 10.4322/acr.2018.092
|View full text |Cite
|
Sign up to set email alerts
|

Monostotic craniofacial fibrous dysplasia: report of two cases with interesting histology

Abstract: Fibrous dysplasia (FD) is a relatively rare osseous disease of unknown etiology, wherein the normal bone is replaced by collagen-rich tissue, comprising of fibroblasts and variably abundant immature woven bone. Clinically, it may involve a single bone or multiple bones. It commonly arises in the jaw bone, skull, rib, and proximal femur. Those arising in the skull and the jaw are together termed “craniofacial fibrous dysplasia.” The differential diagnosis at this location includes meningioma and metastatic carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Singh et al also reported a patient who had suffered from deterioration of vision in the left eye for 1.5 years. Postoperatively the patient improved cosmetically, but the patient’s vision recovered marginally [ 8 ]. Reviewing the cases of acute vision loss from hours to weeks, the visual acuity of the patients recovered well after optic nerve decompression [ 3 , 9 – 12 ].…”
Section: Discussion and Conclusion And Review Of Literaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Singh et al also reported a patient who had suffered from deterioration of vision in the left eye for 1.5 years. Postoperatively the patient improved cosmetically, but the patient’s vision recovered marginally [ 8 ]. Reviewing the cases of acute vision loss from hours to weeks, the visual acuity of the patients recovered well after optic nerve decompression [ 3 , 9 – 12 ].…”
Section: Discussion and Conclusion And Review Of Literaturesmentioning
confidence: 99%
“…Reviewing the cases of acute vision loss from hours to weeks, the visual acuity of the patients recovered well after optic nerve decompression [ 3 , 9 – 12 ]. However, patients with a gradual loss of vision over years are not able to get better visual acuity after optic nerve decompression [ 8 , 13 , 14 ].…”
Section: Discussion and Conclusion And Review Of Literaturesmentioning
confidence: 99%
“…Leur efficacité à augmenter la densité osseuse locale et à prévenir les complications n´est pas démontrée [ 1 , 2 ]. La chirurgie est indiquée dans des cas précis de DFO crânio-faciale (maladie symptomatique, en cas de troubles neurosensoriels ou à visée esthétique) [ 2 , 6 , 8 , 10 ]. Elle sera partielle voire radicale, suivie d´une reconstruction dans les localisations qui le permettent (voûte crânienne, os frontal, maxillaire, mandibule) [ 2 ]; ailleurs, elle sera décompressive en cas d´atteinte de certains organes nobles de la base du crâne (nerf optique, ganglion trigéminal, orbite, conduit auditif externe) [ 2 ].…”
Section: Discussionunclassified
“…La transformation maligne sarcomateuse est possible dans 1% des cas, surtout dans la forme polyostotique [ 3 , 4 ]. Dans tous les cas, la surveillance doit être régulière, prolongée, multidisciplinaire impliquant ophtalmologistes, ORL, orthopédistes, neurochirurgiens, endocrinologues et psychologues [ 7 , 8 , 10 ].…”
Section: Discussionunclassified
“…Depending on the anatomic location in cranio-maxillo-facial area, facial asymmetry, deformity, headache, pathological fractures, nerve de icits, orbital swelling, dental complications when the maxillary or the mandible is involved. And in more severe cases diplopia, proptosis, sinus infection, deafness, and loss of vision, increasing swelling, unusual severity of pains are some of the clinical features [11][12][13][14]. Thus, representing the major clinical manifestations of the disease.…”
Section: Clinical Featuresmentioning
confidence: 99%